Implementasi Automatic Dependent Surveillance Broadcast (ADS-B) di Indonesia - Yati Nurhayati; Susanti Susanti (WARTA ARDHIA, 2014)
Teknlologi ADSB is a new technology in the observation plane which is a combination of global positioning system (GPS), so that the aircraft can be traced to the position, velocity, wind direction, and altitude. This tool can be installed in the aircraft or ground stations and more superior than the radar.ADS-B is indeed a revolutionary look, start with only the antenna and the tool less than for a small refrigerator can detect aircraft and air traffic displays.Automatic Dependent Surveillance- Broadcast (ADS-B) is a detection technology where each plane passing owned transponder emits every two times per second information altitude, position, speed, direction, and other information to ground stations and other aircraft. This information is obtained from the information the Global Positioning System (GPS) or backup Flight Management System (FMS) in each plane. Teknlologi ADSB adalah teknologi baru dalam pengamatan pesawat terbang yang merupakan kombinasi global positioning system (GPS), sehingga pesawat bisa terlacak posisi, kecepatan, arah angin, dan ketinggian. Alat ini bisa dipasang di pesawat atau stasiun darat dan lebih unggul dari radar. ADS-B ini memang terlihat revolusioner, dengan hanya berbekal antenna dan alat kurang dari sebesar lemari es kecil dapat mendeteksi pesawat terbang dan menampilkan lalu lintas udara.Automatic Dependent Surveillance- Broadcast (ADS-B) adalah teknologi pendeteksi dimana setiap pesawat lewat transponder yang dimiliki memancarkan setiap dua kali dalam tiap detik informasi ketinggian, posisi, kecepatan, arah, dan informasi lainnya ke stasiun darat dan pesawat lainnya. Informasi ini didapat dari informasi Global Positioning System (GPS) atau backup Flight Management System (FMS) yang ada di pesawat masing-masing.